Seasonal variations in HbA1c among type 2 diabetes patients on a semi-arid climate between the years 2005–2015 - Raphael, Allon (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2021)
• Seasonal variations of HbA1c occur in semi-arid climates under certain conditions. • We found HbA1c spring peak in some subpopulations, as noted by other researchers. • The HbA1c peak in some subpopulations occurs in the summer, a unique finding. • Hot weather adversely affects some diabetes patients, like cold rainy weather. • Recognition of this pattern could help patients and physicians with diabetes care.